Radiology resident education during the COVID-19 pandemic in the United States - Mohammed I. Quraishi; Alan Itkin; Alexandria Atkins; Benjamin Davis; Robert Eric Heidel; Mark Andrew Rowley; Ethan Nussio; Richard Gray (Frontiers in Medicine)
The COVID-19 pandemic presented unprecedented challenges to healthcare systems, including radiology residency programs. This study aims to examine the impact of COVID-19 on radiology residency education and identify interventions implemented for future unplanned disruptions to physician training. Data collection occurred between March to April 2022 through a survey distributed to 30 radiology residency program directors from diverse geographic regions, hospital types, and practice settings. Data was collected on program characteristics, COVID-19 impact, changes in scheduling and teaching methods, and perceived effects on resident competence and well-being. All surveyed programs implemented changes to address resident teaching to accommodate social distancing. Most programs (86.7%) offered remote work/study options. A majority (66.7%) implemented alternating resident schedules. Virtual conferences and virtual view-box teaching were identified as the most utilized interventions during social distancing requirements. The majority (76.1%) of programs reported worsened resident education during the pandemic, with first-year residents the most adversely affected group. Decreased competence was noted in 40% of first-year and 36.7% of second-year residents compared to pre-pandemic cohorts. Additionally, a significant portion (73.3%) of program directors reported negative impacts on resident well-being. The COVID-19 pandemic significantly disrupted radiology residency despite mitigation efforts. While virtual teaching methods provided necessary alternatives during the pandemic, they could not fully replace traditional in-person education, as evidence by widespread reports of worsened educational outcomes. Recommendations for future preparedness include prioritizing early deployment of remote workstations, incorporating alternative teaching methods, providing increased on-site instruction for junior residents, and enhancing mental health support. These lessons can inform strategies to better prepare residency programs for future challenges and ensure the continued production of competent, resilient radiologists.